Pedagogical Practices of a Special Educator: Engaging Parents Who Have Children With Intensive Needs (LEARNing Landscapes, 2021)
As a special education teacher working with intensive needs children and their families, I have come to understand the importance of using “parent knowledge” alongside my professional knowledge to inform my pedagogy, enabling me to authentically and meaningfully program for students. In this article, I use my storied experiences with Shirley and her mom, Nancy, to make visible how my engagement with Nancy shaped my beliefs and practices as a teacher. This article describes a “pedagogy of walking alongside,” a pedagogical approach in which parent engagement is integral in all work I do with young intensive needs students.
Keywords: parent engagement; parent knowledge; early childhood education; special education